Analisis Tingkat Religiusitas Pada Mahasiswa Yang Mengikuti Organisasi - Dony Darma Sagita; Dede Miftah Fauzi; Jumadi Mori Salam Tuasikal (PEDAGOGIKA, 2021)
This study is aims to describe of religious level by students who follow the organization. The study uses a quantitative descriptive study method. The withdrawal of samples in this research uses sampling, by cluster sampling techniques. The findings suggest that the religiosity of the student who attends the organization falls at a high rating of 28%, and a high category of 66%. This suggests that most research subjects have high religious levels. Therefore, effort is required for students who join the organization to maintain religiosity